Coding variants in RPL3L and MYZAP increase risk of atrial fibrillation - Thorolfsdottir, Rosa B; Sveinbjornsson, Gardar; Sulem, Patrick; Nielsen, Jonas B.; Jonsson, Stefan; Halldorsson, Gisli H; Melsted, Pall; Ivarsdottir, Erna V; Davidsson, Olafur B; Kristjansson, Ragnar P; Thorleifsson, Gudmar; Helgadottir, Anna; et al. (Communications Biology, 2018)
Source at https://doi.org/10.1038/s42003-018-0068-9. Most sequence variants identified hitherto in genome-wide association studies (GWAS) of atrial fibrillation are common, non-coding variants associated with risk through unknown mechanisms. We performed a meta-analysis of GWAS of atrial fibrillation among 29,502 cases and 767,760 controls from Iceland and the UK Biobank with follow-up in samples from Norway and the US, focusing on low-frequency coding and splice variants aiming to identify causal genes. We observe associations with one missense (OR = 1.20) and one splice-donor variant (OR = 1.50) in RPL3L, the first ribosomal gene implicated in atrial fibrillation to our knowledge. Analysis of 167 RNA samples from the right atrium reveals that the splice-donor variant in RPL3L results in exon skipping. We also observe an association with a missense variant in MYZAP (OR = 1.38), encoding a component of the intercalated discs of cardiomyocytes. Both discoveries emphasize the close relationship between the mechanical and electrical function of the heart.